Noninvasive Neurally Adjusted Ventilatory Assist in Premature Infants Postextubation - Colaizy, Tarah T.; Kummet, Gary J.; Kummet, Colleen M.; Klein, Jonathan M. (American Journal of Perinatology, 2017)
Background Neurally adjusted ventilatory assist (NAVA) has distinct advantages when used invasively compared with conventional ventilation techniques. Evidence supporting the use of noninvasive NAVA is less robust, especially in the very low birth weight (VLBW) population.Objective To determine whether synchronized noninvasive ventilation via neurally adjusted ventilatory assist (NIV NAVA) supports ventilation postextubation in premature infants.Methods A retrospective analysis of a cohort of twenty-four former VLBW (<1.5 kg) infants from July 2011 to October 2012. Decreased or unchanged capillary pCO2 after increasing NAVA support was used as a marker for adequately supported noninvasive ventilation. The Wilcoxon signed-rank test was used to compare pre- and post-NAVA intervention (α = 0.05).Results Ventilation improved after an increase in NIV NAVA level in 83% of the premature infants studied (20/24) with a decrease in median pCO2 by 5 mm Hg (p = 0.0001).Conclusion NIV NAVA can provide synchronized postextubation ventilatory support as measured by decreased pCO2 in premature infants.
Keywords: neurally adjusted ventilatory assist; noninvasive ventilation; very low birth weight